Clinical Effects of Microwave Ablation in the Treatment of Low-Risk Papillary Thyroid Microcarcinomas and Related Histopathological Changes - Lu, Chenya; Li, Xingjia; Chu, Xiaoqiu; Li, Ruiping; Li, Jie; Wang, Jianhua; Wang, Yalin; Xu, Yang; Chen, Guofang; Xu, Shuhang; Liu, Chao (Frontiers in Endocrinology, 2021)
Objective This study aimed to evaluate the feasibility and efficacy of ultrasound-guided percutaneous microwave ablation (MWA) in the treatment of low-risk papillary thyroid microcarcinoma (PTMC), and to observe the histopathological changes after MWA. Methods MWA was performed under ultrasound guidance for 73 unifocal PTMC patients without clinically cervical or distant metastasis. The target ablation zone exceeded the tumor edge (judged by contrast-enhanced US) to avoid marginal residue and recurrence. Ultrasound evaluation was performed at 1 day, 1, 3, 6, 12 and 24 months after treatment, and thyroid function evaluation at the first 6 months. Repeated fine needle aspiration cytology or core needle biopsy pathology was performed at 3 or 6 months after MWA to evaluate residual tumors. Any adverse event associated with MWA was evaluated. Results The follow-up after MWA lasted 6 (6, 12) months. Tumor volume decreased significantly from 0.06 mm3 (0.04, 0.11 mm3) to 0.03 mm3 (0.00, 0.06 mm3) at 12 months after MWA (P< 0.001), with a median volume reduction ratio of 80.28% (-7.43, 100%) and 16 cases (21.92%) presenting complete remission. The largest diameter, volume and ablation energy were found to be different in patients with and without complete remission 12 months after MWA. On histopathological examinations, no atypical or malignant follicular cells were identified after thermal ablation. The most common pathological characteristics were fibroblastic proliferation (34/39, 87.18%) and chronic inflammation (32/39, 82.05%), followed by infarction (21/39, 53.85%). Five patients were transferred to thyroidectomy and 4 of them were confirmed with local recurrence and/or lymph node metastasis. Serum thyrotropin decreased transiently after MWA (P< 0.01) but normalized thereafter. No serious and permanent complications were reported. Conclusions MWA is a safe and effective treatment for low-risk PTMC. Fibroblastic proliferation and chronic inflammation are the most common pathological changes after MWA of PTMC.